Pengaruh Indepedensi, Pengalaman Audit, dan Keahlian Profesional Auditor terhadap Kualitas Audit - Dita Dwi Ariyanti; Reni Farwitawati (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to examine the influence of auditor independence, audit experience, and professional expertise on audit quality in Public Accounting Firms located in Bali Province. Using a quantitative research design, data was collected through a structured questionnaire given to 30 active auditors selected by purposive sampling. All variables were measured using a five-point Likert scale, and data were analyzed using multiple linear regression. The findings show that the regression model is statistically significant, suggesting that independence, audit experience, and professional expertise together affect audit quality. The main results of the study show that professional expertise is the only variable that has a significant positive effect on audit quality, while audit independence and experience do not show partial significance. These results show that technical competence, mastery of standards, and professional capabilities play an important role in improving the effectiveness of audit procedures and the ability of auditors to detect material misrepresentations. This study concludes that strengthening the professional expertise of auditors is very important to improve audit quality. The implications of this study highlight the importance for Public Accounting Firms to optimize auditor development programs to ensure reliable financial reporting and maintain public trust.